MEASURING EFFECTIVENESS OF ARABIC INSTRUCTIONAL MEDIA IN ARABIC SENIOR HIGH SCHOOLS IN BRUNEI DARUSSALAM: A STUDY AT GRADE ELEVEN / Ø§ÙƒØªØ´Ø§Ù ÙØ¹Ø§Ù„ÙŠØ© Ø§Ù„ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ø§Ù„Ù…Ø¯Ø§Ø³ Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ø¨Ø±ÙˆÙ†Ø§ÙŠ Ø¯Ø§Ø± Ø§Ù„Ø³Ù„Ø§Ù…: Ø§Ù„ØµÙ Ø§Ù„ØØ§Ø¯ÙŠ Ø¹Ø´Ø± Ù†Ù…ÙˆØ°Ø¬Ø§ - Achmad Yani; Siti Sara Binti Haji Ahmad; Nurul â€˜Ain Binti Haji Ismail; Muhammad Amil Zayyan Bin Haji Abd as-Samad; Nurul Aqilah Binti Jawrami (Lughawiyah: Journal of Arabic Education and Linguistics, 2021)
This study aims to measure the effectiveness of Arabic instructional media used in eleventh grade of Arabic senior high schools in Brunei Darussalam. This study was quantitative and evaluative study. The researchers distributed questionnaires to all Arabic teachers who teach grade eleven students in the schools. The data then were analyzed quantitatively and having evaluative analysis. Based on data analysis, it was found that the instructional media used to teach Arabic language in grade eleven has advantages and disadvantages. The advantages are the availability of modern and various media (87.5%), most of the media are appropriate for the students’ age and cognitive level (87.5%), all media are interesting and helpful for Arabic language skills (100%), and most of the teachers often use the media (87.5%). While, the weaknesses are there is still few media that is not as modern as it is expected (12.5%) such as language laboratory, a few media is not appropriate for the students (12.5%), and there are still some teachers who do not use the media frequently (12.5%).